2021
DOI: 10.3390/met11050734
|View full text |Cite
|
Sign up to set email alerts
|

Application of Eh-pH Diagrams on Acid Leaching Systems for the Recovery of REEs from Bastnaesite, Monazite and Xenotime

Abstract: Bastnaesite, monazite and xenotime are rare earth minerals (REMs) that are typical sources for rare earth elements (REEs). To advance the understanding of their leaching and precipitation behavior in different hydrometallurgical processes, Eh-pH diagrams were constructed and modified using the HSC 9.9 software. The aqueous stability of rare earth elements in H2O and acid leaching systems, i.e., the REE-Ligands-H2O systems, were depicted and studied based on the Eh-pH diagrams. This study considers the most rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…(Table 4). The low extraction efficiency of Ce, Nd, and Th can be explained by the formation of insoluble compounds at high pH and Eh values, as was shown by Lin P. et al [48]. Sorption or extraction methods can be used to recover REEs from the resulting solution to increase the pregnant solution's concentration before REEs precipitation [28].…”
Section: Study Of the Kinetics And Mechanism Of Sc Leaching From Rmfmentioning
confidence: 98%
“…(Table 4). The low extraction efficiency of Ce, Nd, and Th can be explained by the formation of insoluble compounds at high pH and Eh values, as was shown by Lin P. et al [48]. Sorption or extraction methods can be used to recover REEs from the resulting solution to increase the pregnant solution's concentration before REEs precipitation [28].…”
Section: Study Of the Kinetics And Mechanism Of Sc Leaching From Rmfmentioning
confidence: 98%
“…Lin et al [35] reported that the reduction in particle size and preliminary alkali and/or thermal activation greatly improved REE extraction from coal-related materials by mineral acids. As can be seen from the RM characterization, the RM-ESPD was already alkali and thermally activated; moreover, its particles were very fine.…”
Section: Red Mud Characterizationmentioning
confidence: 99%
“…As was shown in the literature [10,13,17] and in our previous research [14], Sc extraction by different acids was very low at pH values higher than 2.5 However, in this work, the extraction of almost all selected REEs was lower than 10% only at a pH of 6. Such low extractions of REEs, Fe, Al, and Ti using diluted acids are connected with the low accessibility of the REEs by H + ions in the solid matrix of iron minerals that remain unleached at this pH, The possible reason for this is connected with the pH of their hydroxides precipitation, i.e., Fe(OH) 3 begins to precipitate at a pH of 3 [35]. Sc(OH) 3 begins to precipitate at a pH higher than 6.…”
Section: Leaching With Mgsomentioning
confidence: 99%
See 1 more Smart Citation
“…(2) no se producen gases residuales durante el proceso, y los subproductos valiosos (el gas de cloro de alta pureza y el gas de hidrógeno) se generan simultáneamente por electrólisis, lo que puede compensar parte del costo de producción (Meng et al, 2020). El principal desafío en el mercado global de REE es aumentar la recuperación de los elementos durante el procesamiento metalúrgico (Lin, Yang, Werner, & Honaker, 2021).…”
Section: Procesamientounclassified